PENINGKATAN KERJA INSULIN DENGAN ACTIVE STRETCHING EXERCISE PADA DMT2 DI KABUPATEN PEKALONGAN - Nurul Aktifah; Firman Faradisi (Universitas Muhammadiyah Kudus, 2019)
Physical exercise can significantly reduce weight and insulin sensitivity; hence, it can reduce blood glucose levels and improve blood glucose control. The main objective of this study was to determine the effectiveness of active stretching exercise to increase the function of insulin on Diabetes Mellitus Type 2(DMT2) at Pekalongan Regency. The design of this study was a randomized controlled trial (RCT) with one-group pretest-posttest design. 20 respondents were chosen by using total sampling technique on August 3 - October 27, 2018. The data collection tools were a questionnaire, GlucoDrTM, and Autocheck®. The Shapiro-Wilk test was implemented as a normality test.To determine the effect of the treatment, a paireddependent T-Test was used. This study found out that there was no significant difference of the work of insulin, before and after the respondents did the active exercise, with a value of ρ 0.315. Therefore, it is strongly recommended that further research applies active stretching exercise combined with 7 self-management of diabetes.